Pengembangan Media Pembelajaran KOTASU untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas VI pada Materi Tata Surya - Putri, Yolanda; Saefurohman, Asep; Juhji, Juhji (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research addresses the challenge of low critical thinking skills among Grade VI students, particularly in science education, specifically the solar system. The limited availability of suitable learning media exacerbates this issue. The study aims to assess the feasibility and effectiveness of KOTASU-based learning media in improving critical thinking skills in this domain. Employing the Research and Development method, the study garnered favorable evaluations from expert panels, with average scores of 4.4, 4.6, and 4.75 from media, material, and language experts, respectively. Student responses, totaling 93.1% in the "Very Valid" category, corroborate the media's efficacy. The N-Gain test results, averaging 0.75 in the "High" category, underscore the substantial improvement in critical thinking skills facilitated by KOTASU learning media. In conclusion, the findings indicate that KOTASU learning media is feasible and highly effective in enhancing students' critical thinking abilities.